A study of CSF idiotypes in multiple sclerosis. - Ebers, G (1982)
Six anti-idiotypic antisera have been raised against isolated cerebrospinal fluid (CSF) bands from five patients with multiple sclerosis and against a serum band from an additional patient. Preparative isoelectric focusing in agarose was useful for isolating highly purified bands. Individual antigenic specificities defined by these antisera were not detected on other bands from the same patients or in IgG isolated from the CSF of other patients. The CSF to serum ratios of the idiotypic determinants ranged from 1:2 to 1:8, consistent with substantial local synthesis in the central nervous system; the higher concentration in serum suggests that initial clonal expansion of antibody-making cells may have occurred outside the nervous system. An anti-idiotypic antiserum raised against the dominant band from postmortem CSF was used to compare the levels of idiotypic IgG eluted from four plaque areas. Although the amount of IgG eluted from each differed, the concentration of idiotype was similar for all plaques tested. The interaction of anti-idiotype with idiotype could not be inhibited by saline extracts of normal or multiple sclerosis brain.